GENETIC VARIABILITY IN WHEAT MEASURED BY PEDIGREE AND MORPHOLOGICAL DISTANCE - BERTAN, Ivandro; VIEIRA, Eduardo Alano; CARVALHO, Fernando Irajá Félix de; COSTA DE OLIVEIRA, Antonio; SCHEEREN, Pedro Luiz; OLIVO, Franciéle (Scientia Agraria, 2007)
Phenotypic and pedigree data are very important tools used by breeders to estimate the genetic distance within and between plant species. Therefore, the objective of this work was to estimate the genetic distance between southern brazilian wheat genotypes, using phenotypic and pedigree data and to establish the degree of association between such techniques. The work was performed in the County of Pelotas, Rio Grande do Sul state, Brazil. Nineteen wheat genotypes were field evaluated for three years, and characterized using 17 morphological traits. These genotypes were used for calculating the phenotypic distance and coancestry coefficient estimates. The results indicate a lack of association between the two evaluated measures of distance, mainly because there is no common ancestor among the tested genotypes, or still, because of lack of pedigree data for some genotypes. Both genetic distance estimates point to the presence of genetic variability among the tested genotypes. These differences can be exploited for recommending hybrid combinations followed by selection of superior genotypes. Genotypes such as BRS 177 and Rubi present high grain yield and are fairly genetically distant from most genotypes according to both measures and should be used in artificial crosses aiming to increase wheat variability and grain yield.